The use and the cost of outpatient diagnostic procedures for cardiovascular diseases in Isfahan province: A utilization study - Reza Rezayatmand; Ghasem Yadegarfar; Masoumeh Ghasemirad; Farzaneh Mohammadi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Cardiovascular diseases (CVDs) are among the most important causes of premature death, disability, disease burden, and increasing the cost of healthcare worldwide. Having an overview of service utilization can help policymakers to plan more effective use of those services and to cut costs. Thus, this study aims to determine the amount of use as well as the cost of various outpatient diagnostic procedures for CVDs in Isfahan province of Iran from 2011 to 2017. MATERIALS AND METHODS: This descriptive study used insurance claim data (time period: 2011-2017) from Health Insurance Organization in Isfahan province to determine the amount of use and the cost of various outpatient diagnostic procedures for CVDs. Afterward, based on these data, the use and the cost of various outpatient diagnostic procedures for CVDs were estimated for the total population of Isfahan province. The list of outpatient diagnostic procedures for CVDs was carefully chosen according to experts' opinions. RESULTS: The use and the cost of outpatient diagnostic procedures for CVDs have drastically increased in the study period (2011-2017). Since 2011, the number of procedures and their related costs have increased 6.6 and 30.76 times (11.74 times, adjusted with PPP conversion factor), respectively. Per capita use (per thousand people) was 18.75 in 2011, reaching 116.51 in 2017. Per capita cost (per thousand people) was 1,887,660 IRR (355 PPP$) in 2011, reaching 54,660,365 IRR (3920 PPP$) in 2017. The highest cost and use were related to echocardiography and electrocardiography, respectively. A notable increase has been observed in the share of radionuclide myocardial perfusion scan and analysis of pacemakers and ICDs of the total cost. CONCLUSIONS: The use of outpatient diagnostic procedures for CVDs has drastically increased during the studied period. Consequently, the cost borne by the health system and the patients have notably increased. This may be because of the increase in the incidence and prevalence of CVDs during the study period. Greater access to related health services can be mentioned as another reason for this increase. Further research is needed to explain all potential reasons and their importance, which can provoke a suitable health policy reaction.